Analisis Motivasi Belajar Siswa pada Pembelajaran PJOK di Sekolah Menengah Kejuruan dengan Pendekatan Self-Determination Theory (SDT) - Yohanes Turnip; Asep Sumpena; Riansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to analyze student learning motivation in Physical Education, Sports, and Health (PJOK) at Vocational High Schools (SMK) using the Self-Determination Theory (SDT) approach, comprehensively based on three basic psychological needs components: autonomy, competence, and relatedness. The research method used is quantitative correlational, involving 55 respondents from grades X and XI students at SMK Telkom Bandung. Based on the multiple linear regression analysis, the variables of autonomy, competence, and relatedness simultaneously have a significant effect on student learning motivation with a significance value of 0.003. However, partially, only the relatedness variable has a significant effect on learning motivation (Sig. = 0.007), while autonomy (Sig. = 0.331) and competence (Sig. = 0.593) do not show a significant effect. Based on these findings, it can be concluded that there is a positive relationship between the fulfillment of the psychological need for relatedness and PJOK learning motivation, making this factor a potential strategy for teachers to consider in facilitating a more optimal learning experience. Keywords: Autonomy, Learning Motivation, Physical Education, Relatedness, Self-Determination Theory